Investigation of drag-reduction effect of super-hydrophilic surface in laminar microchannel flow - Luo, Haoyu (2022)
In previous studies of newly fabricated surface-coating materials, the super hydrophilic surface etched by Cu2+/HNO3 exerts higher drag-reduction effect at low Reynolds numbers than the modified superhydrophobic surface even with similar surface structure. In this paper, both experimental and modelling fluid dynamics studies are used to invest the drag-reduction and flow field for these super hydrophilic surfaces in the microchannel. The experimental results showed that the drag-reduction rate would gradually decrease with the velocity increment of medium. Besides, the dissolved gas does play a key role in reducing the shear stress in the near wall flow field by forming the non-shear air/water interface and increasing its wall-slippage effect. Moreover, the flow-field stimulation analysis provides more intuitive schematic diagram velocity magnitude and pressure changes inside the microchannel, and the surface roughness obtained by chemical etching is capable to enhance the drag-reduction effect as well.